Ultra-Short Duration Hypothermia Prevents Intracranial Pressure Elevation Following Ischaemic Stroke in Rats - Omileke, Daniel; Pepperall, Debbie; Bothwell, Steven W.; Mackovski, Nikolce; Azarpeykan, Sara; Beard, Daniel J.; Coupland, Kirsten; Patabendige, Adjanie; Spratt, Neil J. (Frontiers in Neurology, 2021)
There is a transient increase in intracranial pressure (ICP) 18–24 h after ischaemic stroke in rats, which is prevented by short-duration hypothermia using rapid cooling methods. Clinical trials of long-duration hypothermia have been limited by feasibility and associated complications, which may be avoided by short-duration cooling. Animal studies have cooled faster than is achievable in patients. We aimed to determine whether gradual cooling at a rate of 2°C/h to 33°C or 1°C/h to 34.5°C, with a 30 min duration at target temperatures, prevented ICP elevation and reduced infarct volume in rats. Transient middle cerebral artery occlusion was performed, followed by gradual cooling to target temperature. Hypothermia to 33°C prevented significant ICP elevation (hypothermia ΔICP = 1.56 ± 2.26 mmHg vs normothermia ΔICP = 8.93 ± 4.82 mmHg; p = 0.02) and reduced infarct volume (hypothermia = 46.4 ± 12.3 mm3 vs normothermia = 85.0 ± 17.5 mm3; p = 0.01). Hypothermia to 34.5°C did not significantly prevent ICP elevation or reduce infarct volume. We showed that gradual cooling to 33°C, at cooling rates achievable in patients, had the same ICP preventative effect as traditional rapid cooling methods. This suggests that this paradigm could be translated to prevent delayed ICP rise in stroke patients.